Assessment of the Factors that Contribute for the Cause of Asthma Disease in Ambo Town - Bekele, Damtew; Atsbeha, Aschalew (Journal of Human Health Research, 2023)
Asthma is a chronic disease of airways; that is widely characterized by an increased responsiveness to a large variety of stimuli, airway inflammation and obstruction. It is the most common respiratory disorder disease in developed and developing countries. The study was aimed to assess the factors that contribute for the cause of asthma disease in Ambo town and cross-sectional survey was conducted to gather information from March to April 2022. 30 respondents were selected using purposive sampling technique for interview and data collections. According to the study the more affected age group were 22-32(53%) and the major risk factor for the disease was air pollution (53%). The pollution is due to domestic wastes that are discharged to the environment. Therefore, the government and extension health workers should aware the community about the risk factors of asthma and proper waste disposal mechanisms.
Keywords: Asthma; Health; Risk factors